루돌프 아른하임의 시각적 사고를 통해 본 비가독적 타이포그래피 기반 무빙포스터 연구 - 강지현; Kang Ji Hyun; 이예승; Yeseung Lee (기초조형학연구, 2023)
이 연구의 목적은 비가독성이 시각적 사고력 향상에 미치는 영향을 비가독적 타이포그래피 기반의 무빙포스터를 중심으로 고찰하는 것이다. 뉴미디어는 인쇄포스터에서 무빙포스터로 표현 영역의 확장을 이끌었다. 이러한 현상은 포스터 디자인의 초점이 ‘정지’에서 ‘움직임’으로 이동함으로써 우리에게 표현의 다양성을 제공함을 시사한다. 무빙포스터는 텍스트와 이미지의 공존, 융합, 해체 등 다양한 방식을 거쳐 비가독성을 유발하며 주목성을 얻었다. 이 연구는 개성 있는 그래픽이 난무하는 시각문화 안에서 사용자의 주체적인 시각정보 습득력, 즉 시각적 사고력 향상 방안을 살피는 것을 목표로 한다. 왜냐하면 시각 언어는 이미지를 통해 정보를 습득하고 타인과 소통하게 하고, 시각정보를 주체적으로 지각, 분석하고 개인의 삶과 연관시켜 시각 경험의 폭을 확장하는 시각적 사고 능력이 현 시각문화를 향유하는 세대가 함양해야 하는 중요한 소양이기 때문이다. 이를 위해 이 연구에서는 무빙 타이포그래피 포스터를 활용하여 비가독적 시각표현이 시각적 사고력 향상에 어떤 영향을 미치는지 탐구했다. 연구 결과는 다음과 같다. 1) 비가독적 타이포그래피 무빙포스터는 시각적 사고력을 향상시킬 수 있는 다양한 시지각 요소로 구성되어 있다. 2) 비가독적 시각표현이 사용된 무빙포스터는 비일상적인 외부 자극으로 사용자의 스키마를 자극하여 흥미와 관심을 유발하고, 장기기억으로 저장될 가능성이 높다. 3) 비가독적 시각언어는 사용자에게 무의미한 시각적 복잡성을 제공하는 것이 아닌, 하나의 독립된 시각언어로서 대중과 소통한다. 4) 무빙포스터 내에서 비가독성을 유발하는 요인으로는 조형요소의 왜곡, 게슈탈트 그루핑의 붕괴, 맥락 벗어나기, 시간적 배치가 활용된다. 이 연구는 최종적으로 시각적 사고력 향상을 위해 비가독적 타이포그래피 무빙포스터가 지닌 비가독성 유발 요소를 찾아 분석 모형을 제시하고 그 활용을 예시를 통해 확인했다는 점에서 의의가 있다. The purpose of this study is to investigate the effect of illegibility on visual thinking skills, focusing on moving posters based on illegible typography. New media has led to the expansion of the field of expression from printed posters to moving posters. This study suggests that the focus of poster design has shifted from ‘stillness’ to ‘movement’, providing us with diversity of expression. Moving posters have gained attention by causing illegibility through various methods such as coexistence, fusion, and deconstruction of text and images. The goal of this study is to improve visual thinking, an user’s ability to get visual information, especially when unique graphics are commonly used in visual culture. It is important because visual language allows us to acquire information and communicate with others through images, while visual thinking, an ability to independently perceive, analyze, and relate visual information to one’s own life and expand the breadth of visual experience, is an important skill to cultivate for the current generation to appreciate today’s visual culture. To accomplish our/the goal, this study explored how illegible visual representations would improve visual thinking skills by utilizing moving typography posters. The results of the study are as follows 1) Illegible typography moving posters consist of various visual perceptual elements that can improve visual thinking skills. 2) Moving posters with illegible visual representations trigger interest and attention, and store in long-term memory as extraordinary and external stimulation causes user’s schema. 3) Illegible visual language communicates with the public as an independent visual language, rather than providing meaningless visual complexity to users. 4) Illegibility within moving posters can be triggered by the use of sculptural elements, distortion of sculptural principles, disruption of Gestalt grouping, defamiliarization, and temporality. The significance of this study is that it finally found the factors that cause illegibility in illegible typographic moving posters, and presented an analytical model and confirmed its use through examples.